The effect of benson relaxation technique on sleep quality and negative emotion in maintenance hemodialysis patients - Wu, Shan-Shan; Chen, Jing-Fang; Yan, Hong-Yun; Wu, Tao-Feng; Li, Xian-Wen; Gu, Qin; Li, Jing; Jiang, Ling; Fang, Xiao-Lan (Frontiers in Psychiatry, 2026)
ObjectiveTo explore the effect of Benson relaxation technique on sleep quality and negative emotion in maintenance hemodialysis patients.MethodA total of 105 patients with end-stage renal disease who underwent maintenance hemodialysis in the hemodialysis center of our hospital from September 1,2024 to April 1,2025 were selected as the research subjects. According to the order of enrollment, they were divided into study group (52 cases) and control group (53 cases). The scores of Pittsburgh sleep quality index (PSQI), self-rating depression scale (SDS), self-rating anxiety scale (SAS), 36-iem short form health survey (SF-36) and serum indexes [5-hydroxytryptamine (5-TH), interleukin-6 (IL-6), dopamine (DA)] before and after intervention were collected and compared.ResultAfter intervention, PSQI score (P<0.001), SAS score (P<0.001) and SDS score (P<0.001) in the study group were lower than those in the control group, and SF-36 score was higher than that in the control group (P<0.001). The scores of PSQI, SAS, SDS and SF-36 in the two groups were improved compared with those before the intervention. After intervention, DA in the study group (P<0.05) was lower than that in control group. There was no significant difference in the levels of IL-6 and 5-TH between the two groups after intervention (P>0.05).ConclusionBenson relaxation technique can improve the sleep quality, anxiety and depression of patients with maintenance hemodialysis, and reduce the inflammatory response. It is an effective way to improve the prognosis and quality of life of patients with maintenance hemodialysis.